The Archive Challenge of Turkish Theatre - ÜMIT, NAZLI MIRAÇ (My University, 2019)
The General Directorate of State Archives in Turkey published Arşiv Belgelerine Göre Osmanh'da Gösteri Sanatları [Performing Arts during the Ottoman Era According to Archival Documents] in 2015 as a compilation of records dating from 15th century to 1920s, covering both the imperial and republican periods. The records vary in content [regular fees paid to puppeteers, storytellers, illusionists; licences provided for theatre buildings; prohibition of staging certain Shakespeare plays ... etc) and they were selected by a small group of senior officials working at the Archives. The publication is neither a critical study of Turkish theatre nor a historical narrative. The visuals of chronologically ordered manuscripts are given with their transcriptions and translations from Ottoman Turkish to modern Turkish. The preface; however, reveals the motives of the editorial board by giving a mild reproof to theatre scholars and practitioners who celebrated the 100th anniversary of the Dariilbedayi - the first conservatory which now runs as a state theatre- in 2014 with exhibitions, publications and memorial ceremonies without consulting the documents in the Archive during the preparation process. The group took initiative to work on these records for the first time in order to raise awareness and interest towards them. However, according to what I was told during the interview conducted with one of the editors, the reception was disappointing since the publication has not received any feedback from theatre scholars yet and the Archive's records on theatre have not been in use as much as they expected. The traces of certain discourses produced by westernisation, romantic nationalism, or ottomanism have been decisive in Turkish theatre historiography. Accordingly, archival research has often been hand in hand with what theatre meant for the historian or what conclusions he wanted to reach at. In some cases for instance, self-orientalism led scholars embrace widely accepted views on 'Islam and performance’ without any further debate on suggested evidences as they needed the exact before and after in their narratives. Or, the memoirs of foreign travelogues have been consulted more than the local records on regulations of coffee house entertainments as the latter’s credibility contradicts with the long-established bias against the history and theatricality of unwritten performances. This paper seeks to question the engagement of Turkish theatre historiography with archives and drawing on the above-mentioned case, it discusses the possible motives and results of that engagement.
Keywords: Ottoman Archives; Turkish Theatre; Turkish Performing Arts; Theatre Historiograpy; Osmanlı Arşivi; Türk Tiyatrosu; Türk Sahne Sanatları; Tiyatro Tarihçiliği